2022
DOI: 10.1097/meg.0000000000002506
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and safety of ustekinumab in Crohn’s disease: a prospective cohort study

Abstract: Background Real-world data showed that ustekinumab is an effective treatment for Crohn's disease for up to 52 weeks. Yet, long-term effectiveness and safety outcomes beyond 52 weeks are limited. This study aimed to evaluate the corticosteroidfree clinical remission for up to 104 weeks. Secondary aims were focused on biochemical disease, dosing adjustments and safety outcomes. Methods This multicentre prospective cohort study enrolled Crohn's disease patients who started ustekinumab between May 2016 and Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Recent prospective data of the Dutch ICC (Initiative on Crohn and Colitis) Registry showed UST treatment probability to be at 64.3% at week 52 and 54.8% at week 104, with loss of response to be the main reason for quitting the drug, and no new safety issues 12 . A different Dutch study with partly the same authors as the ICC Registry study found a 59% drug survival probability at week 104 18 . The dose escalation rate was 33% at the end of year 1 and 15% at year 2.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent prospective data of the Dutch ICC (Initiative on Crohn and Colitis) Registry showed UST treatment probability to be at 64.3% at week 52 and 54.8% at week 104, with loss of response to be the main reason for quitting the drug, and no new safety issues 12 . A different Dutch study with partly the same authors as the ICC Registry study found a 59% drug survival probability at week 104 18 . The dose escalation rate was 33% at the end of year 1 and 15% at year 2.…”
Section: Discussionmentioning
confidence: 93%
“…The few 2-year studies concluded with all-over similar findings to the results we publish here. Recent multicenter prospective data revealed clinical remission rates, as per the HBI, to be at 40.0% at year 1 and 40.4% at year 2, and steroid-free remission rates to be 35% and 35.5%, respectively 18 . The low but still present steroid use observed in our cohort (12.8%, 7.4%, and 5.4%) allows us to believe our steroid-free remission rates correspond to this degree (exact values for this variable of our cohort are not shown here).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have utilized real-world data to assess the long-term effectiveness and persistence of ustekinumab maintenance therapy. 28 41 However, real-world data of objectively assessed disease activity, such as faecal markers and endoscopic outcomes, are limited. 10 , 18 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%